DETERMINAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PROGRAM KELUARGA BERENCANA - Dewi Indriani; Efriza Efriza; Adriani Suwito (Universitas Fort De Kock, 2022)
Long-term contraceptive methods have a higher level of effectiveness than other family planning methods. Types of MKJP are IUD, implant, MOW and MOP. The MKJP coverage of West Pasaman Regency in 2020 is only 21.3% and has not reached the set target of 40.5%. This study aims to determine the determinants of the selection of long-term contraceptive methods. This research is a mix method research at February 2022 in West Pasaman District. The population is couples of childbearing age. The sample size is 99 people. The informants is 32. Data were collected by means of interviews and documentation studies. The data that has been collected is processed and analyzed computerized using the Chi Square test. The results Chi Square get p value 0.023 (age), 0.015 (JKN ownership), 0.001 (education), 0.009 (knowledge), 0.003 (attitude), 0.029 (perception), 0.000 (family support), 0.001 (role of health workers) , and 0.023 (culture). The result of logistic regression test is pvalue 0.007 and OR 5.657. Based on the results of the study, the most influential variable on MKJP is age, knowledge, role of health workers and family support . It is recommended that the West Pasaman DPPKBP3A should establish good and sustainable coordination with relevant agencies in order to provide education and motivate couples of childbearing age to participate in using MKJP Keyword : MKJP, determinant